The legal protection of women from violence: normative gaps in international law - Jones, Jackie; Manjoo, Rashida (Human rights and international law, 2019)
The importance of international law and institutions (Jackie Jones) -- Exploring the consequences of the normative gap in legal protections addressing violence against women (David richards and Jillienne Haglund) -- Normative developments on violence against women in the United Nations System (Rashida Manjoo) -- The African human rights system : challenges and potential in addressing violence against women in Africa (Nicholas Wasonga Orago and Maria Nassali) -- The European system : Convention on Human Rights (ECHR) and the Council of Europe Convention on Violence against Women and Domestic Violence (Istanbul Convention) (Jackie Jones) -- Violence against women : normative developments in the Inter-American Human Rights System (Caroline Bettinger-Lopez) -- Closing the normative gap in international law on violence against women : developments, initiatives, and possible options (Rashida Manjoo)